THE BLOOD PICTURE OF HARD-LIPPED BARB [Osteochilus hasselti CV] THAT INFECTED BY Aeromonas hydrophila BACTERIA - Sukandar, Anjas Friyana; Mulyana, Mulyana; Mumpuni, Fia Sri (Universitas Djuanda Bogor, 2018)
The experimental research was carried out on March to August, 2018, at The Fisheries Laboratory, Djuanda University, Bogor. The research is aimed to know and analyze the blood picture of hard-lipped barb that infected by Aeromonas hydrophila.Â The experimental research used complete randomized design with 7 treatments and each 2 replications. The treatments are Control (without A. hydrophila injection), A (with 104 cfu/mL injection), B (with 105 cfu/mL injection),Â C (with 106 cfu/mL injection), D (with 107 cfu/mL injection), E (with 108 cfu/mL injection), and F (with 109 cfu/mL injection). The other than Control treatment, each fish in the experimental research was injected via intramuscular with a virulen strain Aeromonas hydrophila bacteria according to the dose of treatment as much as 0.1 mL. The results of research showed that total erythrocytes 1,01 x 106 sel/mm3-1,31 x 106 sel/mm3 and the hemoglobin 2,3 g%-5,2 g% levels have experienced decrease, while total leucocytes 4,32 x 104 sel/mm3-7,53 x 104 sel/mm3 have experienced increase andÂ hematocrite 19,2%-21,4% levels were stable.